Developing multimodal literacy in tertiary education. Issue 4 (2nd October 2018) - Papadopoulou, Maria; Goria, Sophia; Manoli, Polyxeni; Pagkourelia, Evgenia
Abstract: During the last few years, there has been an ongoing interest in applying multimodality in educational practice, while the need to develop future educators' multimodal literacy has become more than necessary. In this context, the present research aimed at exploring whether a multimodal literacy course could contribute to university student multimodal literacy development and help them implement multimodality in early childhood educational settings. The sample of the study consisted of 20 Greek undergraduate students of the Department of Early Childhood Education of the University of Thessaly, who completed an online questionnaire. Moreover, seven students, seven out of 20 participated in a focus-group discussion. The data were analysed through the thematic analysis method. The results of the study indicated that the course had a positive impact on raising student's multimodal literacy and awareness of applying multimodal pedagogies in schools.